Pulmonary renal syndrome: A case report of diffuse alveolar hemorrhage in association with ANCA negative pauci-immune glomerulonephritis. Issue 23 (June 2018) - Saladi, Lakshmi; Shaikh, Danial; Saad, Muhammad; Cancio-Rodriguez, Enny; D'Agati, Vivette D.; Medvedovsky, Boris; Uday, Kalpana A.; Adrish, Muhammad
Abstract: Rationale: Pulmonary renal syndrome (PRS) is a term most commonly used to describe a combination of glomerulonephritis and pulmonary hemorrhage as a manifestation of a multisystem autoimmune disease. It is usually associated with ANCA vasculitis and anti-GBM disease. Diffuse alveolar hemorrhage in a patient with ANCA and anti-GBM negative pauci-immune glomerulonephritis is rare and optimal management is unknown. Patient concerns: An 85-year-old man with hypertension, diabetes mellitus, prostate cancer and recently diagnosed pauci-immune necrotizing glomerulonephritis presented to our emergency department with worsening dyspnea and pedal edema for several days. Clinical presentation and radiological studies were suggestive of fluid overload but he developed worsening respiratory failure despite hemodialysis. Diagnoses: Bronchoscopy confirmed diffuse alveolar hemorrhage. ANCA and anti-GBM antibodies were negative. The patient was diagnosed with pulmonary renal syndrome – diffuse alveolar hemorrhage in the setting of ANCA and anti-GBM negative pauci-immune glomerulonephritis. Interventions: Patient was started on intravenous pulse steroids, cyclophosphamide and received seven sessions of plasmapheresis. Outcomes: There was an improvement in patient's respiratory status and repeat bronchoscopy at the end of treatment did not show diffuse alveolar hemorrhage. Lessons: Pauci-immune crescentic necrotizing glomerulonephritis is usually associated with the presence of ANCA, however, ANCA may be absent in 10% of these cases. Immunosuppression is the mainstay of treatment for ANCA and anti-GBM associated PRS. This case highlights the importance of immunosuppression and plasmapheresis in patients with ANCA negative vasculitis due to presence of unidentified serum antibodies. If left untreated, these patients can have a fulminant course with high mortality ranging from 25 to 50%.